2013
DOI: 10.1002/aoc.3045
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and efficient catalysis system for the synthesis of 4‐vinylbiphenyl derivatives

Abstract: A series of 4‐vinylbiphenyl derivatives were synthesized by Pd(OAc)2/PCy3‐catalyzed Suzuki–Miyaura reaction in the presence of K3PO4.3H2O as base in toluene at 80°C for only 10–30 min, and the corresponding products achieved 65–98% yields. According to this efficient C―C bond‐forming method, the obtained yields of 4‐vinylbiphenyl liquid crystal compounds were up to 92–96%. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Inspired by this study and based on our previous studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], we reported Pd-catalyzed, highly selective C(sp 2 )-Br bond coupling reactions of o -(or m -, or p -)chloromethyl bromobenzene with arylboronic acids in the presence of the ligand PCy 3 ·HBF 4 , which does not afford C(sp 3 )–C(sp 2 ) coupling products; instead, the reaction provided highly selective of C(sp 2 )–C(sp 2 ) coupling products ( Scheme 1 b).…”
Section: Introductionmentioning
confidence: 98%
“…Inspired by this study and based on our previous studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], we reported Pd-catalyzed, highly selective C(sp 2 )-Br bond coupling reactions of o -(or m -, or p -)chloromethyl bromobenzene with arylboronic acids in the presence of the ligand PCy 3 ·HBF 4 , which does not afford C(sp 3 )–C(sp 2 ) coupling products; instead, the reaction provided highly selective of C(sp 2 )–C(sp 2 ) coupling products ( Scheme 1 b).…”
Section: Introductionmentioning
confidence: 98%
“…McCluskey et al 8 reported the synthesis of substituted 4-vinylbiphenyl monomers by 1 mol % Pd(DIPHOS) 2 -catalyzed Suzuki-Miyaura reactions, but this catalysis reaction was carried out under the microwave-assisted condition at 100 °C, and 4-vinylphenylboronic acid as a bifunctional substrate is prone to give the undesired homo-coupling product at high temperature. Based on our previous research works [9][10][11][12][13][14] , herein we report a simple and efficient approach for the synthesis of 4-vinylbiphenyl derivatives by Pd(II)-1,2-diaminocyclohexane complex catalyzed Suzuki-Miyaura reactions.…”
Section: Introductionmentioning
confidence: 99%